Afghanistanas Younger, Elite, and Educated Population: A Cultural Assessment and Possible Implications for the Economic and Political Future of the Country (Global Journal of Management and Business Research, 2013)
This paper is an exploration of the cultural values of the younger, elite segment of Afghani culture using the Hofstede-Bond typology. Afghanistan was not included in Hofstede's original or subsequent studies, and there is a dearth of empirically-based literature on the cultural classification of this country. The results of this study indicate that this segment of the Afghanistan population is low in power distance, highly masculine, slightly individualistic, somewhat accepting of uncertainty, and possesses a short term orientation towards time. The paper also compares these values with other cultures in the region and beyond, and explains how these cultural differences could hold some promise for this war-torn country. Implications for economic and political development are discussed.